Study on factors that influencing job satisfaction among nurses in KPJ Ampang Puteri Specialist Hospital / Nur Fadilatul Aishah Mohd Noh and Raja Nur Maisarah Raja Amir Shah - Mohd Noh, Nur Fadilatul Aishah; Raja Amir Shah, Raja Nur Maisarah (2013)
In the era of the intense competition and strong-survive business environment has fostered business firms to not only attract but more importantly to retain the workers within their business environment. Every head of services are been pressure to ensure that their nurses have a conducive work environment that may link to job satisfaction and good outcomes. Many firms, no exception for healthcare business, strive to differentiate themselves from the rest of the competitors. Retaining workers especially nurses which we focus in this research is somewhat much lower cost than to acquire new workers. This paper investigates and determines the factors that have possibility to influence job satisfaction especially among nurses. It consists of investigating the factors that might influence nurse’s job satisfaction in their workplace. The factors might influence job satisfaction among nurses is working environment, compensation and career development. The finding presented will focus on the main issue. This study was conducted at KPJ Ampang Puteri Specialist Hospital. All nurses working were the target subject. Suggestions for future studies in decreasing nurse’s job dissatisfaction were discussed.